Combination of novel systemic agents and radiotherapy for solid tumors – Part II: An AIRO (Italian association of radiotherapy and clinical oncology) overview focused on treatment toxicity. (February 2019) - Arcangeli, Stefano; Jereczek-Fossa, Barbara Alicia; Alongi, Filippo; Aristei, Cynthia; Becherini, Carlotta; Belgioia, Liliana; Buglione, Michela; Caravatta, Luciana; D'Angelillo, Rolando Maria; Filippi, Andrea Riccardo; Fiore, Michele; Genovesi, Domenico; et al.
Abstract: Clinical development and use of novel systemic agents in combination with radiotherapy (RT) is at nowadays most advanced in the field of treatment of solid tumors. Although for many of these substances preclinical studies provide sufficient evidences on their principal capability to enhance radiation effects, the majority of them have not been investigated in even phase I clinical trials for safety in the context of RT. In clinical practice, unexpected acute and late side effects may emerge especially in combination with RT. As a matter of fact, despite combined modality treatment holds potential for enhancing the therapeutic ratio, some concerns are raised from the lack of high-quality clinical data to guide the care of patients who are treated with novel compounds in conjunction with RT. The aim of this review is to provide, from a radio-oncological point of view, an overview of the most advanced combined treatment concepts for solid tumors focusing on treatment toxicity.